Nutrient Imbalances in agricultural development - Vitousek, P.M.; Naylor, RL; Crews, T; David, M.B.; Drinkwater, L.E.; Holland, E; Johnes, PJ; Katzenberger, J; Martinelli, LA; Matson, PA; Nziguheba, Generose; Ojima, DS; et al. (American Association for the Advancement of Science, 2009)
Nutrient additions to intensive agricultural systems range from inadequate to excessive—and both extremes have substantial human and environmental costs.